Analisis Kinerja Keuangan Pemerintah Daerah Kabupaten Langkat Provinsi Sumatera Utara - Fadli, Ahmad; Marliyah, Marliyah; Hasibuan, Nur Fadhilah Ahmad (Universitas Labuhanbatu, 2024)
This study aims to determine the level of financial performance in the Government of Langkat regency, North Sumatra province. The Data used is the Financial Report of the Langkat regency Regional Government in 2018-2020. The analysis technique used uses five ratios, namely the ratio of regional financial independence, effectiveness ratio, efficiency ratio, compatibility ratio and growth ratio. The results showed that the financial independence ratio of Langkat regency has a very low performance, the effectiveness ratio is in the effective area, the efficiency ratio is not effective, the ratio of harmony/activity is not good and the growth ratio has a negative value.